THU0551 SOCIAL CARE USE IN PEOPLE WITH CHRONIC PAIN IN THE UNITED KINGDOM. (2nd June 2020) - Humphreys, J.; Dempsey, K.; Phelan, O.; Boothman, L.; Cook, L.; Dixon, W.
Abstract : Background: Chronic pain is a common and disabling health problem and those affected may need support with their activities of daily living (ADLs). Currently there are no data quantifying how much social care support people with chronic pain need. Objectives: To describe formal and informal social care use in people with chronic pain Methods: Between June-July 2019, previous participants of the Cloudy with a Chance of Pain study were invited to take part in an online survey, adapted from a validated Personal Social Services Research Unit interview survey. It collected data on whether participants with chronic pain needed help with ADLs, how frequently help was needed and who provided it (formal and informal social care). Additional data was collected on demographics, employment status, pain diagnosis, and comorbidities. Descriptive statistics described the burden of social care need and multivariable logistic regression identified factors associated with social care need. Results: There were 981 respondents; 791 (81%) were female, median age 59 years (table 1 ). In the last month 527(61%) respondents reported needing help with ADLs. Over three-quarters of help was provided informally by family and friends (408 (77%)). For 309 (59%) respondents, help was needed at least daily. In the multivariable logistic regression model, needing help was lower with older age, (OR (95% CI) 0.96 (0.94-0.98), but higher in female gender (OR (95% CI) 1.96 (1.27-3.01), fibromyalgia (OR(95% CI) 2.75(2.53-5.54)), osteoarthritis (OR (95% CI) 1.56 (1.11-2.19)) and multi-morbidity OR (95% CI) 2.13 (1.51-3.01)). Compared to full-time work, respondents who were retired or unable to work were also significantly more likely to need help with ADLs, respective OR (95% CI) 2.16 (1.21-3.84) and 6.98 (3.72-13.08). Conclusion: A high proportion of people with chronic pain needed support with ADLs; for more than half, on a daily or more frequent basis. Interestingly, younger patients were more likely to need help which may reflect responder bias (younger patients with severe pain potentially more likely to respond than those with milder pain). The majority of support was provided informally, and this could be for a number of reasons. For example, lack of awareness/not meeting eligibility/unable to afford formal social care, or preference to be cared for by familiar persons. This should be explored in future research. These results demonstrate the burden of social care may be significantly greater than government and social care organisations are aware, with important implications for policy and planning. Disclosure of Interests: Jenny Humphreys: None declared, Katy Dempsey: None declared, Ollie Phelan: None declared, Laura Boothman: None declared, Louise Cook: None declared, William Dixon Consultant of: Bayer and Google